Reproductive history and pancreatic cancer incidence and mortality in a cohort of post-menopausal women - Stevens, Richard J (2009)
There is inconsistent evidence about the effect of reproductive history on women’s risk of pancreatic cancer. In the Million Women Study, a prospective cohort of middle-aged women in the UK, we examined associations between reproductive history and pancreatic cancer incidence and mortality, controlling for age, socioeconomic status, geographic region, body mass index, smoking and history of diabetes. During 7.1 million person-years of follow-up in 995,192 post-menopausal women there were 1,182 incident pancreatic cancers. Pancreatic cancer incidence and mortality did not vary significantly with age at menarche, number of children, age at first birth, breastfeeding, type of menopause, age at menopause or time since menopause. Any effect of reproductive history and pancreatic cancer risk in women is likely to be weak, if it exists at all.